Greg,
The form you want has the variable y on the left side and x on the right side so I would first subtract 2x from each side.
2x + 3y = 7
3y = 2x + 7
The coefficient of y is to be 1 so divide both sides by 3
y = ^{2}/_{3} x + ^{7}/_{3}
If you now subtract ^{7}/_{3} from each side you have an equation of the required form.
y  ^{7}/_{3} = ^{2}/_{3} x, in other words
y  ^{7}/_{3} = ^{2}/_{3} (x  0)
There are other possibilities for x1 and y1, For example in the equation y = ^{2}/_{3} x + ^{7}/_{3} if you write ^{7}/_{3} as
^{9}/_{3}  ^{2}/_{3 }= 3  ^{2}/_{3} then
y = ^{2}/_{3} x + ^{7}/_{3}
y = ^{2}/_{3} x + 3  ^{2}/_{3}
y = ^{2}/_{3} (x  1) + 3
y  3 = ^{2}/_{3} (x  1)
Penny
